The Role Of Psychologist Services In Ensuring Social Adaptation Of Children In Preschool Educational Institutions - Nosirova, Muhabbat (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
This article examines the psychological barriers that arise during the adaptation of preschool children to the kindergarten environment and the role of the institution's psychologist in overcoming them. The importance of cooperation between the psychologist, educator and parents for the successful entry of the child into the social environment is analyzed.